Impact of pulmonary hypertension on outcomes after TEER in patients suffering from mitral regurgitation - Jaeger, Philippa; Toskas, Ioannis; Henes, Jessica-Kristin; Shcherbyna, Serhii; Schwarz, Frederic; Euper, Miriam; Seizer, Peter; Langer, Harald; May, Andreas E.; Geisler, Tobias; Gawaz, Meinrad; Schreieck, Jürgen; et al. (Clinical research in cardiology, 2024)
Aim: Data on associations of invasively determined hemodynamic parameters with procedural success and outcomes in patients suffering from mitral regurgitation (MR) undergoing transcatheter edge-to-edge repair of the mitral valve (M-TEER) is limited. Methods and results: We enrolled 239 patients with symptomatic MR of grade 2 + , who received M-TEER. All patients underwent extensive pre-interventional invasive hemodynamic measurements via right heart catheterization (mean pulmonary arterial pressure (mPAP), systolic- (PAPsys) and diastolic pulmonary arterial pressure (PAPdia), pulmonary arterial wedge pressure (PAWP), a-wave, v-wave, pulmonary vascular resistance (PVR), transpulmonary pressure gradient (TPG), cardiac index (CI), stroke volume index (SVI)). mPAP and PAWP at baseline were neither associated with procedural success, immediate reduction of MR, nor residual MR after 6 months of follow-up. The composite outcome (All-cause mortality (ACM) and/or heart failure induced rehospitalization (HFH)) and HFH differed significantly after M-TEER when stratified according to mPAP, PAWP, PAPdia, a-wave and v-wave. ACM was not associated with the afore mentioned parameters. Neither PVR, TPG, CI nor SVI were associated with the composite outcome and HFH, respectively. In multivariable analyses, PAWP was independently associated with the composite outcome and HFH. PVR and SVI were not associated with outcomes. Conclusion: PAWP at baseline was significantly and independently associated with HFH and might serve as a valuable parameter for identifying patients at high risk for HFH after M-TEER. ACM and procedural success were not affected by pulmonary arterial pressure before M-TEER. We suggest that the post-capillary component of PH serves as the driving force behind the risk of HFH.
Online veröffentlicht: 02. April 2024
Gesehen am 28.10.2024